Chromatin remodelling factor Brg1 is required for Schwann cell differentiation and myelination. - Weider, Matthias; Küspert, Melanie; Bischof, Melanie; Müller, Jana; Hillgärtner, Simone; Wegner, Michael; et al. (Developmental Cell, 2012)
Schwann cells produce myelin sheaths and thereby permit rapid saltatory conductance in the vertebrate peripheral nervous system. Their stepwise differentiation from neural crest cells is driven by a defined set of transcription factors. How this is linked to chromatin changes is not well understood. Here we show that the glial transcription factor Sox10 functions in Schwann cells by recruiting Brg1-containing chromatin-remodeling complexes via Baf60a to regulatory regions of Oct6 and Krox20 genes. It thereby stimulates expression of these transcriptional regulators that then cooperate with Sox10 to convert immature into myelinating Schwann cells. The functional interaction between Sox10 and Brg1 is evident from gain- and loss-of-function studies, similar neuropathies in the corresponding mouse mutants, and an aggravated neuropathy in compound mutants. Our results demonstrate that the transcription factor-mediated recruitment of the chromatin-remodeling machinery to specific genomic loci is an essential driving force for Schwann cell differentiation and myelination. © 2012 Elsevier Inc.
UnivIS-Import:2015-03-09:Pub.2012.med.IB.LPCIPDBI.chroma

Differential activity of transcription factor Sox9 in early and adult oligodendroglial progenitor cells - Hassel, Lisa; Fröb, Franziska; Küspert, Melanie; Hillgärtner, Simone; Arnold, Philipp; Huang, Wenhui; Kirchhoff, Frank; Wegner, Michael (Glia, 2023)
The high-mobility-group domain-containing transcription factor Sox9 confers glial competence to neuroepithelial precursors in the developing central nervous system and is an important determinant of astroglial and oligodendroglial specification. In oligodendroglial cells, it remains expressed in oligodendrocyte progenitor cells (OPCs) of the developing nervous system, but is shut off in differentiating oligodendrocytes as well as in OPCs that persist in the adult nervous system. To better understand the role of Sox9 in OPCs, we generated mouse models that allowed oligodendroglial expression of a Sox9 transgene during development or in the adult. With transgene expression beginning in the last trimester of pregnancy, the number of OPCs increased dramatically, followed by comparable gains in the number of pre-myelinating and myelinating oligodendrocytes as assessed by marker gene expression. This argues that Sox9 boosts oligodendrogenesis during ontogenetic development at all stages, including terminal oligodendrocyte differentiation. When Sox9 transgene expression started in the adult, many transgene-expressing OPCs failed to maintain their progenitor cell identity and instead converted into myelinating oligodendrocytes. As infrequent and inefficient differentiation of adult OPCs is one of the main obstacles to effective remyelination in demyelinating diseases such as Multiple Sclerosis, increased Sox9 levels in adult OPCs may substantially increase their remyelination capacity.
CRIS-Team Scopus Importer:2023-04-21
Keywords: glia; HMG; myelin; oligodendrocyte; Sox; Sry

Ep400 deficiency in Schwann cells causes persistent expression of early developmental regulators and peripheral neuropathy - Fröb, Franziska; Sock, Elisabeth; Tamm, Ernst. R.; Saur, Anna-Lena; Hillgärtner, Simone; Williams, Trevor J.; Fujii, Toshihiro; Fukunaga, Rikiro; Wegner, Michael (Nature Communications, 2019)
Schwann cells ensure efficient nerve impulse conduction in the peripheral nervous system. Their development is accompanied by defined chromatin changes, including variant histone deposition and redistribution. To study the importance of variant histones for Schwann cell development, we altered their genomic distribution by conditionally deleting Ep400, the central subunit of the Tip60/Ep400 complex. Ep400 absence causes peripheral neuropathy in mice, characterized by terminal differentiation defects in myelinating and non-myelinating Schwann cells and immune cell activation. Variant histone H2A.Z is differently distributed throughout the genome and remains at promoters of Tfap2a, Pax3 and other transcriptional regulator genes with transient function at earlier developmental stages. Tfap2a deletion in Ep400-deficient Schwann cells causes a partial rescue arguing that continued expression of early regulators mediates the phenotypic defects. Our results show that proper genomic distribution of variant histones is essential for Schwann cell differentiation, and assign importance to Ep400-containing chromatin remodelers in the process.
CRIS-Team WoS Importer:2019-06-18

KLF9 and KLF13 transcription factors boost myelin gene expression in oligodendrocytes as partners of SOX10 and MYRF - Bernhardt, Celine; Sock, Elisabeth; Fröb, Franziska; Hillgärtner, Simone; Nemer, Mona; Wegner, Michael (Nucleic Acids Research, 2022)
Differentiated oligodendrocytes produce myelin and thereby ensure rapid nerve impulse conduction and efficient information processing in the vertebrate central nervous system. The Kruppel-like transcription factor KLF9 enhances oligodendrocyte differentiation in culture, but appears dispensable in vivo. Its mode of action and role within the oligodendroglial gene regulatory network are unclear. Here we show that KLF9 shares its expression in differentiating oligodendrocytes with the closely related KLF13 protein. Both KLF9 and KLF13 bind to regulatory regions of genes that are important for oligodendrocyte differentiation and equally recognized by the central differentiation promoting transcription factors SOX10 and MYRF. KLF9 and KLF13 physically interact and synergistically activate oligodendrocyte-specific regulatory regions with SOX10 and MYRF. Similar to KLF9, KLF13 promotes differentiation and myelination in primary oligodendroglial cultures. Oligodendrocyte differentiation is also altered in KLF13-deficient mice as demonstrated by a transiently reduced myelin gene expression during the first postnatal week. Considering mouse phenotypes, the similarities in expression pattern and genomic binding and the behaviour in functional assays, KLF9 and KLF13 are important and largely redundant components of the gene regulatory network in charge of oligodendrocyte differentiation and myelination.
CRIS-Team WoS Importer:2022-11-11

Nfat/calcineurin signaling promotes oligodendrocyte differentiation and myelination by transcription factor network tuning. - Weider, Matthias; Starost, Laura Julia; Groll, Katharina; Küspert, Melanie; Sock, Elisabeth; Wedel, Miriam; Fröb, Franziska; Schmitt, Christian; Baroti, Tina; Hartwig, Anna; Hillgärtner, Simone; Piefke, Sandra; et al. (Nature Communications, 2018)
Oligodendrocytes produce myelin for rapid transmission and saltatory conduction of action potentials in the vertebrate central nervous system. Activation of the myelination program requires several transcription factors including Sox10, Olig2, and Nkx2.2. Functional interactions among them are poorly understood and important components of the regulatory network are still unknown. Here, we identify Nfat proteins as Sox10 targets and regulators of oligodendroglial differentiation in rodents and humans. Overall levels and nuclear fraction increase during differentiation. Inhibition of Nfat activity impedes oligodendrocyte differentiation in vitro and in vivo. On a molecular level, Nfat proteins cooperate with Sox10 to relieve reciprocal repression of Olig2 and Nkx2.2 as precondition for oligodendroglial differentiation and myelination. As Nfat activity depends on calcium-dependent activation of calcineurin signaling, regulatory network and oligodendroglial differentiation become sensitive to calcium signals. NFAT proteins are also detected in human oligodendrocytes, downregulated in active multiple sclerosis lesions and thus likely relevant in demyelinating disease.
UnivIS-Import:2018-09-11:Pub.2018.med.IB.LPCIPDBI.nfatca

Nkx2.2 is a direct target gene of Sox10 in oligodendroglia - Weider, Matthias; Schmitt, Christian; Hillgärtner, Simone; Wegner, Michael (2017)
EVALuna2:33484

Publisher Correction: Nfat/calcineurin signaling promotes oligodendrocyte differentiation and myelination by transcription factor network tuning - Weider, Matthias; Starost, Laura Julia; Groll, Katharina; Küspert, Melanie; Sock, Elisabeth; Wedel, Miriam; Fröb, Franziska; Schmitt, Christian; Baroti, Tina; Hartwig, Anna; Hillgärtner, Simone; Piefke, Sandra; et al. (Nature Communications, 2018)
The originally published version of this Article omitted Tanja Kuhlmann and Michael Wegner as jointly supervising authors. This has now been corrected in both the PDF and HTML versions of the Article.
EVALuna2:35744

Sox10 Activity and the Timing of Schwann Cell Differentiation Are Controlled by a Tle4-Dependent Negative Feedback Loop - Aberle, Tim; Walter, Anna; Piefke, Sandra; Hillgärtner, Simone; Wüst, Hannah; Wegner, Michael; Küspert, Melanie (International Journal of Molecular Sciences, 2024)
The HMG-domain containing transcription factor Sox10 plays a crucial role in regulating Schwann cell survival and differentiation and is expressed throughout the entire Schwann cell lineage. While its importance in peripheral myelination is well established, little is known about its role in the early stages of Schwann cell development. In a search for direct target genes of Sox10 in Schwann cell precursors, the transcriptional co-repressor Tle4 was identified. At least two regions upstream of the Tle4 gene appear involved in mediating the Sox10-dependent activation. Once induced, Tle4 works in tandem with the bHLH transcriptional repressor Hes1 and exerts a dual inhibitory effect on Sox10 by preventing the Sox10 protein from transcriptionally activating maturation genes and by suppressing Sox10 expression through known enhancers of the gene. This mechanism establishes a regulatory barrier that prevents premature activation of factors involved in differentiation and myelin formation by Sox10 in immature Schwann cells. The identification of Tle4 as a critical downstream target of Sox10 sheds light on the gene regulatory network in the early phases of Schwann cell development. It unravels an elaborate regulatory circuitry that fine-tunes the timing and extent of Schwann cell differentiation and myelin gene expression.
CRIS-Team Scopus Importer:2024-06-07
Keywords: glia; HMG; Schwann cells; Sox10; transcriptional regulation

Sox9 overexpression exerts multiple stage-dependent effects on mouse spinal cord development - Vogel, Julia; Weider, Matthias; Engler, Lisa; Hillgärtner, Simone; Schmitt, Christian; Hermans-Borgmeyer, Irm; Wegner, Michael (Glia, 2019)
The high-mobility-group (HMG)-domain protein Sox9 is one of few transcription factors implicated in gliogenesis in the vertebrate central nervous system. To further study the role of Sox9 in early spinal cord development, we generated a mouse that allows expression of Sox9 in a temporally and spatially controlled manner. Using this mouse, we show that premature Sox9 expression in neural precursor cells disrupted the neuroepithelium of the ventricular zone. Sox9 also compromised development and survival of neuronal precursors and neurons. Additionally, we observed in these mice substantial increases in oligodendroglial and astroglial cells. Reversing the normal order of appearance of essential transcriptional regulators during oligodendrogenesis, Sox10 preceded Olig2. Our study reinforces the notion that Sox9 has a strong gliogenic activity. It also argues that Sox9 expression has to be tightly controlled to prevent negative effects on early spinal cord structure and neuronal development.
CRIS-Team WoS Importer:2019-11-26

The transcription factor Sox5 modulates Sox10 function during melanocyte development. - Stolt, Claus; Hillgärtner, Simone; Wegner, Michael; et al. (Nucleic Acids Research, 2008)
The transcription factor Sox5 has previously been shown in chicken to be expressed in early neural crest cells and neural crest-derived peripheral glia. Here, we show in mouse that Sox5 expression also continues after neural crest specification in the melanocyte lineage. Despite its continued expression, Sox5 has little impact on melanocyte development on its own as generation of melanoblasts and melanocytes is unaltered in Sox5-deficient mice. Loss of Sox5, however, partially rescued the strongly reduced melanoblast generation and marker gene expression in Sox10 heterozygous mice arguing that Sox5 functions in the melanocyte lineage by modulating Sox10 activity. This modulatory activity involved Sox5 binding and recruitment of CtBP2 and HDAC1 to the regulatory regions of melanocytic Sox10 target genes and direct inhibition of Sox10-dependent promoter activation. Both binding site competition and recruitment of corepressors thus help Sox5 to modulate the activity of Sox10 in the melanocyte lineage.
UnivIS-Import:2015-03-09:Pub.2008.med.IB.LPCIPDBI.thetra

Transcription factor Olig2 is a major downstream effector of histone demethylase Phf8 during oligodendroglial development - Kremp, Marco; Aberle, Tim; Sock, Elisabeth; Bohl, Bettina; Hillgärtner, Simone; Winkler, Jürgen; Wegner, Michael (Glia, 2024)
The plant homeodomain finger protein Phf8 is a histone demethylase implicated by mutation in mice and humans in neural crest defects and neurodevelopmental disturbances. Considering its widespread expression in cell types of the central nervous system, we set out to determine the role of Phf8 in oligodendroglial cells to clarify whether oligodendroglial defects are a possible contributing factor to Phf8-dependent neurodevelopmental disorders. Using loss- and gain-of-function approaches in oligodendroglial cell lines and primary cell cultures, we show that Phf8 promotes the proliferation of rodent oligodendrocyte progenitor cells and impairs their differentiation to oligodendrocytes. Intriguingly, Phf8 has a strong positive impact on Olig2 expression by acting on several regulatory regions of the gene and changing their histone modification profile. Taking the influence of Olig2 levels on oligodendroglial proliferation and differentiation into account, Olig2 likely acts as an important downstream effector of Phf8 in these cells. In line with such an effector function, ectopic Olig2 expression in Phf8-deficient cells rescues the proliferation defect. Additionally, generation of human oligodendrocytes from induced pluripotent stem cells did not require PHF8 in a system that relies on forced expression of Olig2 during oligodendroglial induction. We conclude that Phf8 may impact nervous system development at least in part through its action in oligodendroglial cells.
CRIS-Team Scopus Importer:2024-07-12
Keywords: chromatin; histone demethylase; myelin; oligodendrocyte; Siderius–Hamel syndrome

Transcription factor Zfp276 drives oligodendroglial differentiation and myelination by switching off the progenitor cell program - Aberle, Tim; Piefke, Sandra; Hillgärtner, Simone; Tamm, Ernst R.; Wegner, Michael; Küspert, Melanie (Nucleic Acids Research, 2022)
In oligodendrocytes of the vertebrate central nervous system a complex network of transcriptional regulators is required to ensure correct and timely myelination of neuronal axons. Here we identify Zfp276, the only mammalian ZAD-domain containing zinc finger protein, as a transcriptional regulator of oligodendrocyte differentiation and central myelination downstream of Sox10. In the central nervous system, Zfp276 is exclusively expressed in mature oligodendrocytes. Oligodendroglial deletion of Zfp276 led to strongly reduced expression of myelin genes in the early postnatal mouse spinal cord. Retroviral overexpression of Zfp276 in cultured oligodendrocyte precursor cells induced precocious expression of maturation markers and myelin genes, further supporting its role in oligodendroglial differentiation. On the molecular level, Zfp276 directly binds to and represses Sox10-dependent gene regulatory regions of immaturity factors and functionally interacts with the transcriptional repressor Zeb2 to enable fast transition of oligodendrocytes to the myelinating stage.
CRIS-Team Scopus Importer:2022-03-11

Voltage-Gated Ion Channels Are Transcriptional Targets of Sox10 during Oligodendrocyte Development - Peters, Christian; Aberle, Tim; Sock, Elisabeth; Brunner, Jessica; Küspert, Melanie; Hillgärtner, Simone; Wüst, Hannah; Wegner, Michael (Cells, 2024)
The transcription factor Sox10 is an important determinant of oligodendroglial identity and influences oligodendroglial development and characteristics at various stages. Starting from RNA-seq data, we here show that the expression of several voltage-gated ion channels with known expression and important function in oligodendroglial cells depends upon Sox10. These include the Nav1.1, Cav2.2, Kv1.1, and Kir4.1 channels. For each of the four encoding genes, we found at least one regulatory region that is activated by Sox10 in vitro and at the same time bound by Sox10 in vivo. Cell-specific deletion of Sox10 in oligodendroglial cells furthermore led to a strong downregulation of all four ion channels in a mouse model and thus in vivo. Our study provides a clear functional link between voltage-gated ion channels and the transcriptional regulatory network in oligodendroglial cells. Furthermore, our study argues that Sox10 exerts at least some of its functions in oligodendrocyte progenitor cells, in myelinating oligodendrocytes, or throughout lineage development via these ion channels. By doing so, we present one way in which oligodendroglial development and properties can be linked to neuronal activity to ensure crosstalk between cell types during the development and function of the central nervous system.
CRIS-Team Scopus Importer:2024-07-26
Keywords: central nervous system; glia; myelin; Sox protein; transcriptional control

Zinc-finger transcription factor Zfp276 acts as a novel regulator of oligodendroglial differentiation - Aberle, Tim; Piefke, Sandra; Hillgärtner, Simone; Schimmel, M.; Tamm, E. R.; Wegner, Michael; Küspert, Melanie (GLIA, 2021)
CRIS-Team WoS Importer:2021-07-16